CODE OF ETHICS: QUALITY OF ELECTION MANAGEMENT TO REGIONAL ELECTIONS IN SIMULAR ELECTIONS IN INDONESIA - Cornelis, Vieta I. (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
The urgency of the implementation of General Elections in a Democratic State in Indonesia is to function for the sustainability of the government system so that it requires an active role from all elements of the Indonesian nation, to realize a General Election that is truly carried out in a structured, systematic and responsible manner with consistent and trustworthy escort or supervision. That’s why things that happen related to the code of ethics for the organizers of the General Election, at the time of the General Election simultaneously and must be properly regulated by the organizers of the democratic party. The research method used in this article is normative legal research or commonly referred to as doctrinal law research that focuses on written regulations (law in book). The findings in this article show that in the future simultaneous general elections in the State of Indonesia, which consists of islands with different ethnicities, cultures, different human resources. One thing is realized that democracy does not guarantee equality of conditions, democracy only guarantees equality of opportunity. This equality is what we must apply so that all people have the same rights and obligations in obtaining the things that are mandated in the administration of state life.